Настоящая жизнь: [роман] / Брендон Тейлор - Тейлор Брендон (Inspiria, 2021)
Содержит нецензурную брань. Экземпляры: ЦБ (20230511) / Инвентарный номер: 58872 / Цена: 491.43 / Сис.шифр: 84(4/8) / Авт.знак: Т 30 / ГРНТИ: 17.82.31 / ББК: 84(7Coe)-44